2013
DOI: 10.3174/ajnr.a3676
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Measures Indicate Fight Exposure-Related Damage to Cerebral White Matter in Boxers and Mixed Martial Arts Fighters

Abstract: BACKGROUND AND PURPOSE: Traumatic brain injury is common in fighting athletes such as boxers, given the frequency of blows to the head. Because DTI is sensitive to microstructural changes in white matter, this technique is often used to investigate white matter integrity in patients with traumatic brain injury. We hypothesized that previous fight exposure would predict DTI abnormalities in fighting athletes after controlling for individual variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 42 publications
1
44
2
2
Order By: Relevance
“…Although these data do not inform us about the absolute maxima and minima of the diffusion metric trajectories because of the absence of measurements between 2 weeks and 2 months postinjury, the statistical trend detected by the between-group analyses at 2 months suggests a minor relapse in the recovery of the structural measures of WM integrity. This finding, taken together with the observed variability in the trajectories of RD and FA between 2 weeks and 2 months, might be reflective of the athletes' exposure to subconcussive hits following return to play (see earlier discussion 11,33,68 ). A more recent study, 87 and the first to relate diffusion measures to biomarkers in athletes with subconcussive hits, reported a positive correlation between the percentage change in football post-minus preseason levels of serum autoantibodies of the astrocytic protein, S100B (considered a peripheral marker of blood-brain barrier dysfunction), and the percentage of voxels with changes in MD during the corresponding time period.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 81%
See 3 more Smart Citations
“…Although these data do not inform us about the absolute maxima and minima of the diffusion metric trajectories because of the absence of measurements between 2 weeks and 2 months postinjury, the statistical trend detected by the between-group analyses at 2 months suggests a minor relapse in the recovery of the structural measures of WM integrity. This finding, taken together with the observed variability in the trajectories of RD and FA between 2 weeks and 2 months, might be reflective of the athletes' exposure to subconcussive hits following return to play (see earlier discussion 11,33,68 ). A more recent study, 87 and the first to relate diffusion measures to biomarkers in athletes with subconcussive hits, reported a positive correlation between the percentage change in football post-minus preseason levels of serum autoantibodies of the astrocytic protein, S100B (considered a peripheral marker of blood-brain barrier dysfunction), and the percentage of voxels with changes in MD during the corresponding time period.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 81%
“…These studies 11,33 suggest that RD might be a potentially sensitive measure to subconcussive hits. A recent DTI study 68 on cerebral WM in 74 boxers and 81 mixed martial arts fighters found that a history of previous knockouts (the ''knockout'' measure includes ''technical knockouts'' with no subsequent LOC) could predict increased RD in the CC, isthmus of the cingulate gyrus, pericalcarine sulcus, the precuneus, and the amygdala in the group of boxers. The same regions had increased MD and decreased FA values.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly sophisticated analysis methods of structural imaging data have been developed enabling measurement of grey matter thickness and density, subcortical volume changes, and white matter microstructure at the voxel level for the whole brain. Recent studies that have applied these methods to participants with concussion from a variety of different sports (predominantly American Football, Football, Ice Hockey, and Mixed Martial Arts) have revealed convergent trends for concussion exposure to be related to reduced cortical thickness (Koerte et al, 2015, Albaugh et al, 2015, Tremblay et al, 2013), smaller subcortical structure volumes (Bernick et al, 2015a, Singh et al, 2014), and altered white matter diffusion metrics (Lancaster et al, 2016, Meier et al, 2015, Stamm et al, 2015, Wilde et al, 2015, Tremblay et al, 2014, Shin et al, 2014, Bazarian et al, 2014, Hart et al, 2013, Virji-Babul et al, 2013). Additionally, these findings have often corresponded to impaired neuropsychological function but appear to be more persistent, suggesting a biomarker of longer-term structural alteration.…”
Section: Introductionmentioning
confidence: 99%